Rehabilitation of the Elderly in Primary Healthcare - Iancu, Mihaela Adela; Dumitra, Gheorghe Gindrovel; Ivanov, Simona Maria; Ivanov, Anda Maria; Sandu, Mihaela Nicoletta; Ticarau, Adriana; Calin, Ramona Dorothea; Popescu, Daniela; Condur, Laura Maria; Popovici, Calin; Kozma, Andrei (Balneo and PRM Research Journal (Online. English ed.), 2025)
Rehabilitation is a fundamental pillar of universal health coverage, alongside health promotion, disease prevention, treatment, and palliative care. As a crucial health indicator following mortality and morbidity, functional optimization is a key outcome of rehabilitation. Traditionally associated with tertiary healthcare facilities due to its complex and multidimensional nature, various models have been proposed to integrate rehabilitation seamlessly into primary healthcare services. The primary goal of rehabilitation is to enhance, maintain, and, when possible, improve an individual's functional capacity. This review explores key aspects of elderly patient assessments conducted by family physicians to recommend appropriate rehabilitation programs. Additionally, it highlights the components of integrated preventive consultations for older adults and suggests tailored approaches based on evaluation outcomes.Collaboration between family physicians and medical rehabilitation specialists is essential for the prevention and treatment of elderly patients. A holistic, patient-centered approach ensures comprehensive care, promoting physical independence, mental well-being, and an improved quality of life.